Acceptance Rates for Pharmacist-Initiated Interventions in Long-Term Care Facilities - Gina L. Carson; Kimberly Crosby; Garrett R. Huxall; Nancy C. Brahm (University of Minnesota Libraries Publishing, 2013)
Objectives: Describe individualized medication interventions, categorize intervention types, and report acceptance rates by prescribers following a pilot medication intervention program in which a pharmacist rounded with the patient care team in long-term care facilities in addition to their traditional medication regimen review (MRR) process. Design: Prospective Chart review Setting: Two primary long-term care (LTC) facilities Participants: Fifty randomly selected patient charts. Inclusion criteria were adult patients (18 years old or older) residing in one of the LTC facilities receiving consultant pharmacist services. Patient charts not meeting inclusion criteria were excluded from the review. Interventions: Recommendations made according to the needs of each patient and categorically reported. Main Outcome Measures: Intervention acceptance rates by prescribers and aggregate reporting for type of medication interventions. Results: For 50 patient charts (68% female, 32% male) 66 interventions were reported. The average patient age was 81.5 years. Approximately 45% of the interventions pertained to drug utilization concerns, and 21% involved pain management. Additional categories included treatment of eye and skin conditions and pharmacotherapy for mental health. A 'nonpharmacotherapy' designation was given to individual interventions not fitting into a larger category. New medications and regimen changes were the most common medication therapy outcomes (42% and 32%, respectively). Overall 92% of all pharmacist interventions were either fully or partially accepted by the prescriber where partial acceptance was defined as implementation of the recommendation with an adjustment. Interventions related to drug utilization or pain management each approached a 93% acceptance rate. Conclusions: The consultant pharmacist provided personalized recommendations following extensive chart review and patient assessment. Our chart review suggests that high prescriber acceptance rates along with medication therapy optimization may produce similar benefits in other LTC facilities.   Type: Original Research